The Economic Integration of Forced Migrants: Evidence for Post‐War Germany. (4th April 2013) - Bauer, Thomas K.; Braun, Sebastian; Kvasnicka, Michael
<x xml:space="preserve">Abstract</x> The flight and expulsion of Germans from Eastern Europe after World War II constitutes one of the largest forced population movements in history. We analyse the economic integration of these migrants and their offspring in West Germany. A quarter century after displacement, first‐generation migrants still tend to fare worse economically. Displaced agricultural workers, however, exhibit higher incomes than comparable natives, as displacement caused large‐scale transitions out of low‐paid agriculture. Differences in economic outcomes of second‐generation migrants resemble those of the first generation.